Entrepreneurial Education for Engineers - Zuraidah, Mohd Zain (Association for Engineering Education in Southeast and East Asia and the Pacific, 2009)
Organized by Association for Engineering Education in Southeast and East Asia and the Pacific Seminar , 8th - 9th December 2003 at Universiti Malaya, Selangor.